2013
DOI: 10.1155/2013/938267
|View full text |Cite
|
Sign up to set email alerts
|

NovelERBB Receptor Feedback Inhibitor 1 (ERRFI1)+ 808 T/G Polymorphism Confers Protective Effect on Diabetic Nephropathy in a Korean Population

Abstract: BACKGROUND: The identification and characterization of the gene, ERRFI1, in diabetes has not been reported. In this study, we evaluated the relationship between ERRFI1 polymorphism and characteristics of type 2 diabetes mellitus (T2DM) in Korea.SUBJECTS AND METHODS: We conduct a case-control study involving T2DM patients (n=342) and controls (n=473).RESULTS: A novel single nucleotide ERRFI1 gene polymorphism at +807(T/G) was found. G genotype frequency was 40.1% in the diabetic group and 42.7% in the control g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Genes include STAR (steroidogenic acute regulatory protein) 152 , IL1RN 153 , AQP5 154 , EGR1 155 , SFTPD (surfactant protein D) 156 , KLF10 157 , PODXL (podocalyxin like) 158 , FOXN3 159 , IL6R 160 , PBX1 161 , APOD (apolipoprotein D) 162 , ACVR2B 163 , CD34 164 , INSR (insulin receptor) 165 , APOA5 166 , STAR (steroidogenic acute regulatory protein) 167 , PDK4 168 , GLS (glutaminase) 169 , FKBP5 170 , SLC6A15 171 , MT2A 172 , SLC38A4 173 , AQP7 174 , ABHD15 175 , ABCA1 176 , ZNRF1 177 , PPP1R3B 178 , MAOA (monoamine oxidase A) 179 , UBE2E2 180 , RNASEK (ribonuclease K) 181 , PREX1 182 , DGKG (diacylglycerol kinase gamma) 183 , POSTN (periostin) 184 , COMP (cartilage oligomeric matrix protein) 185 , GAP43 186 , P2RY12 187 , SELL (selectin L) 188 and DLG2 189 were related to type 2 diabetes mellitus. Expression of ERRFI1 190 , ALOX12 191 , SOCS5 192 , DDIT4 193 , DUSP4 194 , IL6ST 195 , DUSP1 196 , SMAD1 197 , NCL (nucleolin) 198 , METTL14 199 , FMOD (fibromodulin) 200 , CYGB (cytoglobin) 201 , UNC5A 202 and TAAR9 203 are believed to be associated with diabetic nephropathy. Genes include FAP (fibroblast activation protein alpha) 204 , EYA4…”
Section: Discussionmentioning
confidence: 99%
“…Genes include STAR (steroidogenic acute regulatory protein) 152 , IL1RN 153 , AQP5 154 , EGR1 155 , SFTPD (surfactant protein D) 156 , KLF10 157 , PODXL (podocalyxin like) 158 , FOXN3 159 , IL6R 160 , PBX1 161 , APOD (apolipoprotein D) 162 , ACVR2B 163 , CD34 164 , INSR (insulin receptor) 165 , APOA5 166 , STAR (steroidogenic acute regulatory protein) 167 , PDK4 168 , GLS (glutaminase) 169 , FKBP5 170 , SLC6A15 171 , MT2A 172 , SLC38A4 173 , AQP7 174 , ABHD15 175 , ABCA1 176 , ZNRF1 177 , PPP1R3B 178 , MAOA (monoamine oxidase A) 179 , UBE2E2 180 , RNASEK (ribonuclease K) 181 , PREX1 182 , DGKG (diacylglycerol kinase gamma) 183 , POSTN (periostin) 184 , COMP (cartilage oligomeric matrix protein) 185 , GAP43 186 , P2RY12 187 , SELL (selectin L) 188 and DLG2 189 were related to type 2 diabetes mellitus. Expression of ERRFI1 190 , ALOX12 191 , SOCS5 192 , DDIT4 193 , DUSP4 194 , IL6ST 195 , DUSP1 196 , SMAD1 197 , NCL (nucleolin) 198 , METTL14 199 , FMOD (fibromodulin) 200 , CYGB (cytoglobin) 201 , UNC5A 202 and TAAR9 203 are believed to be associated with diabetic nephropathy. Genes include FAP (fibroblast activation protein alpha) 204 , EYA4…”
Section: Discussionmentioning
confidence: 99%
“…STAR (steroidogenic acute regulatory protein) [153], IL1RN [154], AQP5 [155], EGR1 [156], SFTPD (surfactant protein D) [157], KLF10 [158], PODXL (podocalyxin like) [159], FOXN3 [160], IL6R [161], PBX1 [162], APOD (apolipoprotein D) [163], ACVR2B [164], CD34 [165], INSR (insulin receptor) [166], APOA5 [167], STAR (steroidogenic acute regulatory protein) [168], PDK4 [169], GLS (glutaminase) [170], FKBP5 [171], SLC6A15 [172], MT2A [173], SLC38A4 [174], AQP7 [175], ABHD15 [176], ABCA1 [177], ZNRF1 [178], PPP1R3B [179], MAOA (monoamine oxidase A) [180], UBE2E2 [181], RNASEK (ribonuclease K) [182], PREX1 [183], DGKG (diacylglycerol kinase gamma) [184], POSTN (periostin) [185], COMP (cartilage oligomeric matrix protein) [186], GAP43 [187], P2RY12 [188], SELL (selectin L) [189] and DLG2 [190] have been revealed to be associated with type 2 diabetes mellitus, but these genes might be novel target for T1DM. Expression of ERRFI1 [191], ALOX12 [192], SOCS5 [193], DDIT4 [194], DUSP4 [195], IL6ST [196], DUSP1 [197], SMAD1 [198], NCL (nucleolin) [199], METTL14 [200], FMOD (fibromodulin) [201], CYGB (cytoglobin) [202], UNC5A [203] and TAAR9 [204] are associated with prognosis in patients with diabetic nephropathy, but these genes might be novel target for T1DM. A previous study reported that FAP (fibroblast activation protein alpha) [205], EYA4 [206], BCL9 [207], IRF2BP2 [208], EGR3 [209], GADD45B [210], DMD (dystrophin) [211], LSR (lipolysis stimulated lipoprotein receptor) [212], DLL4 [213], SUN2 [214], SOS1 [215], PIK3CA [216], GAMT (guanidinoacetate N-methyltransferase) [217], RBM47 […”
Section: Discussionmentioning
confidence: 99%
“…Suppressor Cholangiocarcinoma [154] promotor Intervertebral disk degeneration [56] Suppressor or promotor Diabetes [4,79,87,[165][166][167][168] Suppressor or promoter Cardiovascular diseases [17,175,176] Positive correlation Dwarfism and longevity [178] Negative correlation Psoriasis [180] Negative correlation Autism [179]…”
Section: Suppressormentioning
confidence: 99%
“…Supporting this notion, Gene 33 expression is strongly induced in a murine model for diabetic nephropathy and was proposed to mediate diabetic renal hypertrophy [ 4 ]. Furthermore, a study based on a Korean population revealed a single nucleotide polymorphism (SNP) in the third intron of the ERRFI1 gene (+808(T/G)) that is negatively associated with diabetic nephropathy [ 165 ]. This SNP is believed to negatively regulate the expression of Gene 33 [ 165 ].…”
Section: Gene 33 and Human Diseasesmentioning
confidence: 99%
See 1 more Smart Citation